2016
DOI: 10.2151/sola.2016-019
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Four-Dimensional LETKF and Ensemble-Based Variational Data Assimilation with Observation Localization

Abstract: In data assimilation for weather forecast, ensemble Kalman filter assumes linearity of the observation operator and Gaussianity of the probability distribution function (PDF) to explicitly solve the analysis. As a method avoiding errors based on these assumptions, we describe a four-dimensional ensemble-based variational method (4D-EnVAR) with observation localization. This formulation differs from that of the four-dimensional local ensemble transform Kalman filter (4D-LETKF) only in two points: (1) not assumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…In the 4D-Var-BenkfL system, it is not necessarily zero even at an analysis grid point away from an observation location because the localization scale is defined by r a and the analysis increment evolves in time according to the model dynamics. Similar difference between 4D-Var and LETKF was also observed in Yokota et al (2016).…”
Section: Single-observation Experimentssupporting
confidence: 82%
“…In the 4D-Var-BenkfL system, it is not necessarily zero even at an analysis grid point away from an observation location because the localization scale is defined by r a and the analysis increment evolves in time according to the model dynamics. Similar difference between 4D-Var and LETKF was also observed in Yokota et al (2016).…”
Section: Single-observation Experimentssupporting
confidence: 82%
“…The quality of an estimate with the 4DEnVar can thus be poor if there are insufficient ensemble members. In practical applications of the 4DEnVar, a localization technique is usually used to avoid this problem (e.g., Buehner, 2005;Liu et al, 2009;Buehner et al, 2010;Yokota et al, 2016). However, the present paper does not consider localization because the focus here is on the basic behavior of the 4DEnVar.…”
Section: The 4d Variational Data Assimilation (4denvar)mentioning
confidence: 99%
“…However, the ensemblebased methods basically seek the solution within a lowerdimensional subspace spanned by the ensemble members. In many applications in atmospheric sciences, it has been demonstrated that the localization of the covariance matrix is useful for coping with high-dimensional problems (e.g., Buehner, 2005;Liu et al, 2009;Buehner et al, 2010;Yokota et al, 2016). However, it has not necessarily been clarified how general high-dimensional problems, in which the localization of the covariance matrix might not be appropriate, can be solved with the ensemble-based algorithm which employs the lower-dimensional approximation based on the ensemble.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of an estimate with the 4DEnVar can thus be poor if there are insufficient ensemble members. In practical applications of the 4DEnVar, a localization technique is usually used to avoid this problem (e.g., Buehner, 2005;Liu et al, 2009;Buehner et al, 2010;Yokota et al, 2016).…”
Section: Introductionmentioning
confidence: 99%